ANALISIS PENGENDALIAN MUTU PRODUKSI MELALUI PENDEKATAN STATISTIC QUALITY CONTROL DALAM RANGKA MENJAGA KUALITAS PRODUK (Studi kasus pada PG. Kebon Agung Malang) - Saiful Arifin; M. Hufron; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT This research was done on PG. Kebon Agung, Malang. The purpose of this research is to analyze the Statistics of production quality control approach through quality control to maintain the quality of the production. This variable uses the production quality control and Statistical approach to quality control. Method of data collection using the study of library science and documentary films. The sample used is the amount of production and the amount of production declined to 12 years 2017. The analysis in this study is a descriptive qualitative analysis by processing raw data using a percentage of rendering, compute the line Centre (Central line), the lower control limit (the limit control), calculate the upper limit control (control over the limit), and map control P by using Microsoft excel 2010 help software.The research found that the percentage of damage production at any period of grinding are very low i.e. under 4%, then in the center line of the calculation can be (CL) of 0.02127, and later in the calculation of the limit control top (UCL) or can be called a maximum extent of damage boundary line of 0.147, as well as on the final stages of the calculation of the 3 sigma i.e. calculation of the lower limit (LCL) in can be the result of 0.10373-in other words the lower boundary line is 0 (zero) because if the limits under control less than 0 (zero) then the down control limits deem 0 (zero). So it can be inferred that the quality control of the production of PG. Kebon Agung in the year 2017 during the milling period 12 has been running very well without any slightest deviation.Keywords: Quality, Seven Tools, Statistical Quality Control.